What to Do When Industry Disruption Threatens Your Career - Groysberg, Boris; Johnson, Whitney; Lin, Eric; Andrus, Garth; Kane, Gerald; Von Hippel, Christiana; Bonnici, Ryan; Duarte, Nancy; Torrance, Andrew; Lovallo, Dan; Kahneman, Daniel; DeMonaco, Harold; et al. (MIT Sloan Management Review, 2019)
Volatility in an industry should concern not only the companies within it but also the people who work for them. To stay ahead of developments that may disrupt your professional life, you must make two evidence-based diagnoses: How volatile is your industry? And what explains the volatility? The answers will equip you to disrupt your own career preemptively.